2008
DOI: 10.1101/gad.503108
|View full text |Cite
|
Sign up to set email alerts
|

DNA helicases Sgs1 and BLM promote DNA double-strand break resection

Abstract: A key cellular response to DNA double-strand breaks (DSBs) is 5-to-3 DSB resection by nucleases to generate regions of ssDNA that then trigger cell cycle checkpoint signaling and DSB repair by homologous recombination (HR). Here, we reveal that in the absence of exonuclease Exo1 activity, deletion or mutation of the Saccharomyces cerevisiae RecQ-family helicase, Sgs1, causes pronounced hypersensitivity to DSB-inducing agents. Moreover, we establish that this reflects severely compromised DSB resection, deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
570
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(614 citation statements)
references
References 33 publications
35
570
0
2
Order By: Relevance
“…We found that whereas the Mre11 complex and CtIP are required for the initial short-range end resection to promote MMEJ, BLM and Exo1 are dispensable for this process but are needed for extended end resection and HR (Fig. 5C) (36,43), thus revealing different genetic requirements for the two distinct end resection steps in mammalian cells. Notably, the need for Mre11 nuclease activity in end resection and HR is different in yeast and mammals.…”
Section: Mmej Is Used To Repair Dsbs Occurring At Collapsed Replicationmentioning
confidence: 94%
“…We found that whereas the Mre11 complex and CtIP are required for the initial short-range end resection to promote MMEJ, BLM and Exo1 are dispensable for this process but are needed for extended end resection and HR (Fig. 5C) (36,43), thus revealing different genetic requirements for the two distinct end resection steps in mammalian cells. Notably, the need for Mre11 nuclease activity in end resection and HR is different in yeast and mammals.…”
Section: Mmej Is Used To Repair Dsbs Occurring At Collapsed Replicationmentioning
confidence: 94%
“…Given that CtIP recruitment is not affected after HP1 knockdown (Fig. 2E), to investigate potential links with other relevant proteins that work downstream CtIP, like the Bloom helicase (BLM) and the exonuclease EXO1, 26,27 will be therefore critical to clarify the role of HP1 proteins during DNA-end resection.…”
Section: Methodsmentioning
confidence: 99%
“…The Sgs1 helicase plays distinct roles in DSB end resection (Gravel et al 2008;Mimitou and Symington 2008;Zhu et al 2008), the DNA replication checkpoint (Frei and Gasser 2000), the control of homeologous recombination (Myung et al 2001), and in Figure 7. Mechanism and specificity of Mph1 action.…”
Section: Discussionmentioning
confidence: 99%